DEMPLOT TEKNOLOGI BIOREEFTEK RAMAH LINGKUNGAN BERBASIS KELOMPOK KERJA MASYARAKAT (POKJAMAS) DI KABUPATEN KONAWE SELATAN - La Ode Abdul Rajab Nadia; Salwiyah Salwiyah; Abdullah Abdullah; Amadhan Takwir; Laode Muhamad Hazairin Nadia (Jurnal Marine Kreatif, 2021)
Damage to coral reefs has resulted in decreased habitat and fish populations in the waters of Staring Bay, therefore an environmentally friendly coral rehabilitation program is needed by community engagement. The objective of this work is to rehabilitate coral reefs through the environmentally friendly bioreeftek technology application based on the Community Working Group (POKJAMAS) in the waters of Staring Bay South Konawe. The method of implementing the program is training to strengthen the capacity of Community Working Groups, manufacture of bioreeftek technology and application of bioreeftek technology in waters. The result of this activity was the formation of 2 group POKJAMAS at the location of community service, The total number of POKJAMAS members who are actively involved is 50 people (33 male and 17 female) POKJAMAS members actively participate in training activities and technology demonstration plot (Demplot). POKJAMAS has succeeded in making 800 units of environmentally friendly bioreeftek. Bioreeftek technology has been deployed in Staring Bay waters at 2 locations are Puasana village and Wawatu village. The technology demonstration plot has contributed to strengthening the capacity of POKJAMAS and enhances community responsibility within improving the condition of coral reefs in the waters of Staring Bay in south konawe.